Inheriting the revolution the first generation of Americans - Appleby, Joyce Oldham 1929-; Hunt, Lynn 1945-; Jacob, Margaret C. 1943- (Belknap Press of Harvard Univ. Press, 2000)
Details the experiences of the first generation of Americans who inherited the independent country, discussing the lives, businesses, and religious freedoms that transformed the country in its early years.
Keywords: Geschichte 1783-1865; Sociaal-economische geschiedenis; Geschichte; Gesellschaft; États-Unis - Conditions sociales - Jusqu'à 1865; États-Unis - Histoire - 1775-1783 (Révolution) - Influence; États-Unis - Histoire - 1783-1865; USA; United States -- History -- 1783-1865; United States -- History -- Revolution, 1775-1783 -- Influence; United States -- Social conditions -- To 1865